2013
DOI: 10.1590/s1519-99402013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Interação genótipo-ambiente em rebanhos nelore da Amazônia Legal

Abstract: A interação genótipo-ambiente (IGA) foi estudada por meio de dois procedimentos distintos, em características produtivas e reprodutivas de bovinos da raça Nelore. Dados de pesos padronizados aos 120 (P120); 210 (P210); 450 (P450) dias de idade, perímetro escrotal aos 450 dias de idade (PE450) e idade ao primeiro parto (IPP), de 211.744 registros de animais Nelore, criados na região da Amazônia Legal, foram utilizados na análise. O efeito da IGA foi estudado por meio de estimativas de herdabilidade e de correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
2
1
2
Order By: Relevance
“…Similar results were given by Lira et al (2013) in studies on genetic trends in the Brazilian Tropical Humid Region, and Matos et al (2013) and Nepomuceno et al (2013) studying GxE using multi-trait model.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were given by Lira et al (2013) in studies on genetic trends in the Brazilian Tropical Humid Region, and Matos et al (2013) and Nepomuceno et al (2013) studying GxE using multi-trait model.…”
Section: Resultssupporting
confidence: 76%
“…These results were higher than those registered by Matos et al (2013) in the Brazilian Amazon region, and by Ambrosini et al (2012) in their GxE analysis under RN in Polled Nellore cattle in northeastern Brazil.…”
Section: Resultscontrasting
confidence: 69%
“…The evaluation of the GEI (Table 4) for the scrotal perimeter demonstrated that no results were found that show the presence of the interaction between the regions studied, rg greater than 0.80 for all the combinations between the three regions. These results are confirmed by Matos et al (2013), Chiaia et al (2015), Lemos et al (2015), and Raidan et al (2015), which evaluated Nellore herds distributed among the different Brazilian regions and found no evidence of interaction, all the studies used the measurements of scrotal perimeter at 18 months. This fact can be explained by the high heritabilities found for the traits, showing less influence of the environment.…”
Section: Resultsmentioning
confidence: 56%
“…Thus, AFC has been included as a selection criterion for the Nellore breed in Brazil. Despite having low heritability, it presents genetic variability and potential to be improved with the use of selection, mainly due to the greater selective intensity applied to the females (MATOS et al, 2013). Genetic variability is confirmed by h² value estimated to be 0.117 (Table 2).…”
Section: Resultsmentioning
confidence: 91%
“…Vieira et al (22) encontraram valores semelhantes, média de 36,26 meses de idade para a raça Nelore. Matos et al (23) relataram valores médios de 37 meses. Tanaka et al (24) relatam médias de 35,08 meses.…”
Section: Resultsunclassified